International experience in stimulating the separate collection of household waste - M. S. Baynova (Управление)
The article presents experience of different countries in promoting separate collection of waste. The purpose of the article is to summarize the scientific conclusions of Russian and foreign scientists in the field of household waste management. The author provides an overview of current scientific publications from Russian and foreign sources on the methods used in different countries to stimulate separate collection of household waste, successful results and problems of implementation, directions of waste management policy. The study evaluates the methods of stimulating separate collection in different countries. The policy of household waste management in Western Europe, the USA and Japan receives a high scientific assessment, the principles of stimulating sepa rate collection are enshrined in legislation. New in the practice of separate waste collection is the search for cost-effective and most environmentally friendly technologies. In the countries of Eastern Europe, changes in traditions and organization of housing and communal services are required to meet the high standards of developed countries. Some countries are implementing separate waste policy elements. China is seeking a comprehensive incentive for separate collection. The scientific assessment of international experience can be used in the formation of a comprehensive waste management policy in Russia.